The painted stork ecology and conservation - Urfi, A. J.; SpringerLink (Online service). (New York, NY Springer New York, 2011)
The painted stork is a large, eye-catching, colonially nesting wading bird found across large parts of South and South East Asia, particularly India and Sri Lanka. Listed as near-threatened by various conservation agencies, the painted stork is a flagship of its endangered habitat, wetlands. The Painted Stork: Ecology and Conservation is an exploration of the biology, status, distribution, sexual size dimorphism, mating patterns, growth and development patterns, and food and foraging ecology of this fascinating species. It also addresses stork-human interface and covers many myths and legends associated with storks. Because this bird is a colony nester, it is an ideal model for studies attempting to unravel the mysteries of avian coloniality and its evolution. Finally, the book discusses various conservation aspects, using the Delhi Zoo colony of painted storks as a case study of the potential for a long-term conservation monitoring program in India.
Foreword -- Preface -- Chapter 1 Introduction -- Chapter 2 Distribution and status -- Chapter 3 Coloniality in storks -- Chapter 4 Life in a colony ? case studies from some North Indian heronries -- Chapter 5 Nesting Ecology -- Chapter 6 Growth stages of the Painted Stork -- Chapter 7 Food and foraging -- Chapter 8 Painted Stork and man -- Chapter 9 Conservation issues -- References -- Appendices -- Author Index -- Subject Index.
Electronic reproduction.
Keywords: Mycteria leucocephala--Ecology.; Mycteria leucocephala--Conservation.; Mycteria--Ecology--South Asia; Mycteria--Ecology--Southeast Asia; Mycteria--Conservation--South Asia; Mycteria--Conservation--Southeast Asia; Electronic books